Enhancing Teacher Professionalism through Amaliyatu-T-Tadris Practices: A Study of Final-Year Students at Kulliyyatul Mu’allimat Al-Islamiyah - Ummah, Lulu' Tazkiyatul; Syam, Aldo Redho; Nurjan, Syarifan; Arifin, Syamsul; Haq, Muhammad Arinal (Sahabat Akademia Group, 2025)
This study investigates the influence of Amaliyatu-t-Tadris activities on the professionalism of prospective teachers at Kulliyyatul Mu’allimat Al-Islamiyah. The research was motivated by the increasing need for qualified teachers in Indonesia and the crucial role of Islamic boarding schools in preparing future educators. Using a quantitative approach with a regression design, primary data were collected from final-year students through a four-point Likert-scale questionnaire. The findings indicate that all items in the questionnaire were valid and reliable, with a Cronbach’s alpha of 0.923 for Amaliyatu-t-Tadris and 0.915 for teacher professionalism. The Pearson correlation test revealed a strong positive relationship between Amaliyatu-t-Tadris activities and teacher professionalism (r = 0.811, p < 0.01). The regression analysis further showed that Amaliyatu-t-Tadris accounted for 65.8% of the variance in prospective teachers’ professionalism. These results demonstrate that structured microteaching practices embedded in Amaliyatu-t-Tadris effectively enhance pedagogical competence, classroom management, communication skills, and professional ethics. The study highlights the significance of integrating practice-based training into teacher education programs in Islamic institutions to cultivate professionalism and educational quality.